Design and selection of alternative embankments to overcome tidal flood (A case study of the construction plan of a tidal embankment at Sayung, Demak) - Lulut Riyan Utomo; Henny Pratiwi Adi; slamet Imam Wahyudi (Pondasi, 2022)
Tidal embankment project in Sayung is one of the construction planning projects of the government. There are three alternatives of embankment designs that may be applied in the construction project; (1) Parapet Wall and Corrugated Concrete Sheet Pile (CCSP) reinforcement, (2) Concrete Wall Embankment with mini pile reinforcement, and (3) Multipurpose Panel System Embankment (SPS). The research was needed to examine the designs to find the fittest. This study aimed to redesign the construction plan of the tidal embankment using Plaxis software. This software was to analyze and determine the safety factors of the three alternative embankment designs. It was stated to be safe because it exceeded the standard of 1.5. One of the three alternative embankments was implemented using the Analytical Hierarchy Process (AHP) method based on predetermined criteria: (1) Aspects of function and benefits, and (2) Aspects of site conditions which include cost and construction process. From the alternative selection using the expert choice program analysis method, the concrete wall embankment with mini-pile reinforcement was the main priority, with a weight value of 45.9%. Meanwhile, the second priority was the Parapet Wall and CCSP Reinforcement with a weight value of 37.2%, and the third choice was the Multipurpose Panel System Embankment (SPS) with a weight of 17%.